1998
DOI: 10.1146/annurev.publhealth.19.1.319
|View full text |Cite
|
Sign up to set email alerts
|

SUCCESSFUL BEHAVIORAL INTERVENTIONS TO PREVENT CANCER: The Example of Skin Cancer

Abstract: Important behavioral sources of risk for cancer have been identified and programs to reduce this risk have been initiated. The most heavily studied behavioral risk is tobacco use, but considerable attention has also gone to prevention of skin cancer by modifying sun exposure. Research has shown a strong link between sun exposure and skin cancer, and opportunities to prevent this cancer by changing behavior should be effective. Unlike unmodifiable sources of risk, sun exposure should be modifiable through behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 58 publications
0
32
0
2
Order By: Relevance
“…There is evidence in both the U.S. and Australia that knowledge of the skin cancersun exposure link and of risk reduction behaviors has increased over the past 15-20 years (Baum & Cohen, 1998;Robinson, Rigel, & Amonette, 1997;The Cancer Council, Australia, 2007). Yet research suggests that young adults in particular continue to receive large amounts of both intentional and incidental UV exposure without adequate protection (Hoegh, Davis, & Manthe, 1999;Robinson et al, 1997).…”
mentioning
confidence: 99%
“…There is evidence in both the U.S. and Australia that knowledge of the skin cancersun exposure link and of risk reduction behaviors has increased over the past 15-20 years (Baum & Cohen, 1998;Robinson, Rigel, & Amonette, 1997;The Cancer Council, Australia, 2007). Yet research suggests that young adults in particular continue to receive large amounts of both intentional and incidental UV exposure without adequate protection (Hoegh, Davis, & Manthe, 1999;Robinson et al, 1997).…”
mentioning
confidence: 99%
“…Nearly half of the adolescents indicated that their skins are sometimes tanned and tanning moderately affects their skin. The previous studies reported that the history of blistering sunburn, even once, in childhood and overexposure to sun increase the risk for skin cancer (Baum and Cohen, 1998;Lowe et al, 2002;Maguire-Eise et al, 2005). It is important that adolescents especially under risk due to types of their skin should be informed about the protective measures against the harmful effects of sun.…”
Section: Discussionmentioning
confidence: 98%
“…Approximately half of the adolescents stated to have fewer than 10 moles in their bodies. In literature, it is reported that having light hair color, blue-green eye color and light skin color and the presence of multiple moles in body increase the risk for skin cancer (Baum and Cohen, 1998;Cokkinides et al, 2002;Emmons et al, 2008;Saridi et al, 2009). Our findings are similar to the results of the study performed by Uysal et al (2004) on 12-15 years of age students in Izmir reported that nearly 35% of students have light eye and skin color and also moles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persuasive, easily understood, and consistent education regarding the high risk for skin cancer and preventive strategies to minimize this risk should be an essential part of the annual transplantation evaluation. 50,51 Multimedia educational resources may enhance patient compliance with prophylactic and preventative interventions. Ideally, close coordination with dermatologists will permit the effective education and administration of preventative and prophylactic therapies and allow early recognition of these common cutaneous neoplasms.…”
Section: Taking a Step Back: Prevention Of Skin Cancermentioning
confidence: 99%